TRADITIONS OF CHILDREN’S FANTASY IN “THE CHRONICLES OF NARNIA” BY C. LEWIS (Scientific journal of the Fergana State University, 2023)
Children's fantasy is a mixture of fantasy and children's literature genres, and has a number of genre features of its own. Using the methods of comparison and functional description, the genre features of children's fantasy literature were analyzed in K. Lewis's “The Chronicles of Narnia” and explained providing examples from the work. The fact that the main characters of the work are children, the educational value of the work, and the fact that its plot consists of the struggle between good and evil are proof that it belongs to the genre of children's fantasy.